Perception and attitudinal factors contributing to periodic deworming of preschool children in an urban slum, Nigeria - Paul Eze; Ujunwa Justina Agu; Chioma Lynda Aniebo; Sergius Alex Agu; Lucky Osaheni Lawani (BMC, 2020)
Abstract Background Over 20 million preschool-age children (PSAC) in Nigeria require periodic chemotherapy (PC) for soil-transmitted helminth (STH) infections. Persistently low coverage for this age group threatens the World Health Organization (WHO) 2030 target for eliminating STH infections. Current strategies for targeting PSAC have been largely ineffective. Hence, PSAC are mostly dewormed by their parents/caregivers. However, little is known of the perception and attitude of parents/caregivers of PSAC to deworming in this setting. Methods A mixed methods design, combining a community-based interviewer-administered questionnaire-survey (n = 433) and focus group discussions (FGD) (n = 43) was used to assess the perceptions and attitudes of mothers to periodic deworming of preschool children aged 2-5 years in Abakpa-Nike, Enugu, Nigeria. Results Coverage of periodic deworming in PSAC is 42% (95% CI: 37.3-46.8%). There is significant difference in the specific knowledge of transmission of STH (AOR = 0.62, 95% CI: 0.48-0.81, p = 0.000), complication of STH infections (AOR = 0.77, 95% CI: 0.61-0.98, p = 0.034), accurate knowledge of deworming frequency (AOR = 0.41, 95% CI: 0.18-0.90, p = 0.026), and knowledge of PC drug, mebendazole (AOR = 0.28, 95% CI: 0.09-0.90, p = 0.031), and pyrantel (AOR = 8.03, 95% CI: 2.22-29.03, p = 0.001) between mothers who periodically deworm their PSAC and those who do not. There is no significant difference in specific knowledge of the symptoms of STH infections (AOR = 0.76, 95% CI: 0.57-1.02, p = 0.069) and PC drug, Albendazole (AOR = 1.00, 95% CI: 0.46-2.11, p = 0.972). FGD revealed misconceptions that are rooted in stark ignorance of the disease. Overall attitude to deworming is positive and favourable. Conclusions Poor coverage of periodic deworming for STH infections in PSAC in this setting are primarily driven by poor specific knowledge of the risks and burden of the infection. Focused health education on the burden and transmission of STH infections could complement existing strategies to improve periodic deworming of PSAC in this setting.